Social involution? : The impact of economic restructuring on the working class in Zambia - Chembe, Martin David (My University, 2008)
Countries in southern Africa have been implementing economic liberalisation policies for over two decades, with the aim of reversing years of economic decline. This process of economic liberalisation has been largely been influenced by the International Monetary Fund (IMF) and the World Bank policy prescription. While the developed world has been piling pressure on countries in the Sub-Saharan region to integrate their national economies into the global economic, different countries have responded differently in opening up their economies. For some, the new economic policy regime has entailed a shift from a state-run economy and focusing more on a free market economy. While some countries have taken a cautious approaching to economic liberalisation, Zambia went for rapid liberalisation, which has led to negative social consequences on employment and the livelihoods of the working class. Through the adoption and implementation of labour market flexibility policies, Zambia and other countries in the region have seen an upswing in new forms of employment such as casual labour, subcontracting and temporary employment, which have no protection and have exposed workers to exploitation. Employment levels have also dropped as the capitalist investors shed off massive numbers of workers in order to reduce labour costs. Local manufacturing industries, in most cases, have been forced to close down and lay-off workers due to unfair competition with cheap imported goods. Liberalisation in developing countries in general and southern Africa in particular, has entailed weakening the role of the state in national economic management. Governments are increasingly succumbing to the dictates of multinationals and are failing to enforce regulatory measures needed to protect the welfare of workers and their working conditions.
Keywords: Zambia; liberalization; social involution; structural adjustment; privatization; Karl Polanyi; Southern Africa